2021
DOI: 10.4149/neo_2020_200617n639
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and validation of prognostic nomograms to predict overall survival and cancer-specific survival for patients with osteosarcoma

Abstract: This study aimed to develop and validate nomograms predicting the survival of osteosarcoma patients from the SEER database and our hospital. Data of 1,066 osteosarcoma patients from the SEER database were randomly divided into a development cohort (n=800) and validation cohort one (n=266). Another cohort of 126 patients from our hospital was utilized as validation cohort two. Univariate and multivariate Cox analyses were performed to identify the independent prognostic factors for overall survival (OS) and can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…feret (minimum diameter) significantly indicated higher chemoresistance. This was consistent with previous reports that increased tumour size prognosticated poor outcome for osteosarcoma [19]. Furthermore, higher tumour circularity indicated higher chemosensitivity in the current study.…”
Section: Discussionsupporting
confidence: 94%
“…feret (minimum diameter) significantly indicated higher chemoresistance. This was consistent with previous reports that increased tumour size prognosticated poor outcome for osteosarcoma [19]. Furthermore, higher tumour circularity indicated higher chemosensitivity in the current study.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, it is generally believed that osteosarcoma patients with DM with higher age had a poorer OS prognosis than younger patients (44). Our study showed that patients as study objects (18,50), while we selected the patient with DM who lacked effective treatment and had a poor prognosis as a research object, which is more specific clinically and has not been studied. Second, our research included fewer clinical variables and had comparable or better AUC values.…”
Section: Discussionmentioning
confidence: 93%
“…As reported in previous studies, old age has been proven to be related with poor survival in patients with breast cancer (15), prostate cancer (16), and osteosarcoma (17). However, the precise cut-off value of age in PMCT remains controversial.…”
Section: Discussionmentioning
confidence: 92%